Knowledge and use of traditional medicinal plants by the Setswana-speaking community of Kimberley, Northern Cape of South Africa - Monakisi, Charlotte M. (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--University of Stellenbosch, 2007.